Health system description and assessment: a review of systematic tools for analyses. (20th October 2021) - Waitzberg, R; Rechel, B; Maresso, A; van Ginneken, E; Quentin, W
Abstract: Introduction: Comparing health systems allows policymakers to benchmark against other countries, and improve processes and performance. A template to guide authors on how to present systems' features and performance in a meaningful manner is the basis for understanding and assessing a country's health system. This study presents an overview of approaches for standardized descriptions and analyses of health systems. Methods: We conceptualized four criteria to define a "template" for our analysis. It must have (1) a framework, (2) a list of indicators, (3) instructions for authors on how to write an informative document, and (4) should cover health systems design and performance. Based on these criteria we searched the academic and grey literature, and the web for templates. Results: We found 29 tools that can be used as templates to describe and assess health systems. While ten tools are comprehensive, 19 tools focus on specific topics such as primary care, universal coverage, and quality of care. Another 21 tools focused on health system performance assessment but cannot serve as templates, as we define it. Most tools were developed by big organizations such as WHO, OECD and USAID. Discussion: New models of governance and accountability are leading to increased interest in health system performance. A good template is key to write documents with an organized, coherent and meaningful description and assessment of a health system while allowing for cross-country comparison. We found ten tools that may serve as models of comprehensive templates, while most tools focus on specific topics or on performance assessment only. Conclusions: This study provides a first-ever overview of templates that analyze health systems features and performance. Future studies could explore successful examples to consolidate a template that may potentially improve analysis and comparison of health systems in order to support policymaking. Key messages: We found ten comprehensive tools for describing and assessing health systems. Our overview may help to improve existing templates by learning from experiences of different organizations.